The body size distribution of Filinia longiseta (Ehrenberg) in different types of small water bodies in the Wielkoposka region - Basińska, Anna; Kuczyńska-Kippen, Natalia; Świdnicki, Kasper (Limnetica, 2010)
The body size distribution of Filinia longiseta (Ehrenberg) in different types of small water bodies in the Wielkoposka region Small water bodies are often characterised by speci c macrophyte species composition and different levels of predation. This may also have an effect on the body size and shape of rotifer specimens. The aim of the study was to determine the relation of the size of rotifer Filinia longiseta (body and appendages length), with respect to three speci c kinds of pond (mid-forest, pastoral and anthropogenically changed) and to three kinds of hydromacrophytes (nymphaeids, elodeids and helophytes) as well as comparatively to the open water zone. The examined water bodies also differed in sh presence or absence. Morphometric analysis of specimens of F. longiseta showed that both factors –the type of water body relating to different land-use in the catchment area as well as the microhabitat type– were signi cant predictors, in uencing their body size and spine length. Filinia longiseta specimens were signi cantly smaller in ponds situated within the pastoral catchment area. The largest specimens were found among stands of nymphaeids, while the smallest were found within the open water zone, which may indicate both the ecological requirements of this species as well as the marked in uence of sh in the unvegetated area.

Distribuci´on de tama˜nos de Filinia longiseta (Ehrenberg) en diferentes tipos de peque˜nas masas de agua en la regi´on de Wielkoposka Las peque˜nas masas de agua est´an caracterizadas a menudo por la composici´on espec´ ca de macr´o tos y diferentes niveles de depredaci´on. Esto puede tener efecto en el tama˜no y la forma de los rot´ feros. El objetivo de este estudio fue determinar las diferencias de tama˜no (longitud del cuerpo y de los ap´endices) del rot´ fero Filinia longiseta en tres tipos de charcas (forestales, de pastizales y antropizadas) y en tres tipos de vegetaci´on sumergida (ninfeidos, elodeidos y hel´o tos) as´ como tambi´en en aguas libres. Las charcas examinadas difer´ an tambi´en por la presencia o no de peces. Los an´alisis morfom´etricos de los individuos de F. longiseta han mostrado que tanto el tipo de charca, seg´un los usos del suelo en el ´area de captaci´on, como el tipo de microhabitat in uencian las longitudes del cuerpo y de los ap´endices. Los individuos de F. longiseta resultaron ser signi cativamente m´as peque˜nos en las charcas situadas en las zonas de pastizales. Las poblaciones con individuos de mayor tama˜no se encontraron en las matas de ninfeidos, mientras que en las de aguas libres se encontraba las constituidas por individuos de menores dimensiones, lo que puede ser debido tanto a las adaptaciones de esta especie a las condiciones del medio como a la reconocida in uencia de los peces en las zonas desprovistas de vegetaci´on.
Keywords: body size; Filinia longiseta; Rotifers; Ponds; Macrophytes